Assessing the reality of entrepreneurial skills for owners of small and medium enterprises (Field study in the Syrian coast) - بلال ريان (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to show the reality of entrepreneurial skills for owners of small and medium enterprises in the Syrian coast, Through a statement of fact of personal skills, problem solving skills, creative thinking skills, leadership skills, and the researcher relied on the descriptive approach as a general approach to research, where the material Scientific studies related to the subject of the research, by relying on previous Arab and foreign studies, Arab and foreign books, periodicals, bulletins and conferences related to the subject of the study, in order to identify all aspects of the studied phenomenon and identify its reality on the ground. The most important Arab and international experiences in this field were reviewed. soft sample was taken from the owners of workers in (small and medium enterprises) in the Syrian coast. The questionnaire was distributed to them in different regions; Where 130 questionnaires were distributed, 120 questionnaires were retrieved, of which 110 were valid for the study, with a response rate of 84.62%. The study concluded that the entrepreneurial skills (personal skills, problem-solving skills, creative thinking skills, and leadership skills) are available to owners of small and medium-sized enterprises in the Syrian coast, but to a low degree, and this corresponds to the results of the four hypotheses branching from the main hypothesis